Ethical (Dis) Comfort in John Maxwell Coetzee’s Age of Iron (1990) - Saliou Dione (LingLit Journal Scientific Journal for Linguistics and Literature, 2022)
This article is concerned with making visible ethical (dis)comfort in John Maxwell Coetzee’s Age of Iron (1990) as it unearths how feelings of comfort and/or discomfort shape the individual when associated with ethics across boundaries of inequality, racism, violence, poverty, injustice rather than with the development trust in government and public institution. The inference here is that one of or the two feelings are necessary found in the individual experiencing directly or indirectly the Apartheid system. Therefore, faced with the humanitarianism system, the ontological assumption that underpins the argument, named the characters involved in the situation of ethical (dis)comfort, rests on the embodied, situated, affective, and creative dimensions of their expressions. Leaning on Aristotle’s rhetorical strategies of ethos, logos and pathos, normative ethical theory, axiology, and onomastics, the article analyzes the shift from moral dis-ease to normative ethics by uncovering the socio-psychological development processes and the creation of a space of consciousness and imagination through the author’s (re)conciliation paradigm and multi-racial nation ideal.